Pathologic and molecular characterization of histomoniasis in peafowl (Pavo cristatus). (March 2017) - Clarke, Lorelei L.; Beckstead, Robert B.; Hayes, Jeffrey R.; Rissi, Daniel R.
Histomonas meleagridis is a flagellate protozoan organism that can cause severe necrotizing typhlitis and hepatitis in gallinaceous birds. Peafowl ( Pavo spp.) have been shown to be susceptible to histomoniasis in experimental settings, but there are few reports of natural histomoniasis in this species. A retrospective study of the archived cases at 2 veterinary diagnostic laboratories in the United States yielded 5 cases of peafowl with gross and histologic findings characteristic of histomoniasis. Lesions included bilateral, transmural fibrinonecrotic typhlitis and multifocal necrotizing hepatitis with associated trophozoites morphologically consistent with H. meleagridis . There was no evidence of Heterakis gallinarum infestation in the studied cases. DNA was extracted from formalin-fixed, paraffin-embedded liver and ceca from all 5 cases and was analyzed using multiple sets of primers with subsequent sequencing and genotyping. Four samples were positive for H. meleagridis, and 1 sample was positive for both H. meleagridis and Tetratrichomonas gallinarum . These results confirm that peafowl develop clinical disease similar to that described previously in other gallinaceous birds infected by H. meleagridis . The role of T. gallinarum remains unknown and further research is necessary to elucidate its role, if any, in the pathogenesis of the observed lesions.